Gender Perceptions of Psychological Empowerment in The Workplace: A Comparative Analysis from Two Cultures - Greg-Victor Obi (International Journal of Business and Social Science Research, 2021)
This study investigates how female and male workers perceive feelings of Psychological Empowerment (PE), using respondents from two different countries with dissimilar cultural power dynamics. Two hundred ten non-managerial bank workers from Nigeria and the United States were selected for this study. A comparative quantitative method was used for this study. Statistical analyses were performed using both spreadsheets and SPSS.  My key research question is designed to determine if there are differences in how female and male employees perceive Psychological Empowerment. Data analysis indicates that in both countries combined, and individually, there is a statistically significant difference in the perception of PE between the female and male respondents. Hence, I propose that the first step toward achieving power equity amongst both genders is to first understand how women and men perceive empowerment at a personal level (Psychological Empowerment).